The United Nations Convention Against Corruption a commentary - Rose, Cecily 1980-; Kubiciel, Michael; Landwehr, Oliver 1971- (Oxford Oxford University Press, 2019)
Provides an article-by-article commentary of the United Nations Convention against Corruption (UNCAC), which entered into force in 2005. Each chapter discusses the relevant travaux préparatoires, the text of the final article, and examples of domestic implementing legislation.
Includes bibliographical references (pages 677-694) and index.
Keywords: United Nations Convention against Corruption -- (2003 October 31).; United Nations Conventin against Corruption; Corruption -- Law and legislation